Trauma and the Myth of Evolving Masculinity in Korean National Films - (:unkn) unknown (My University, 2022)
Much more Korean media content is now circulating globally as streaming services allow easier access to various films and shows. In this climate, it seems pertinent to ask what makes a film or TV show marked “Korean” on Netflix inherently Korean. The popular TV show is not fully depicting Korea but representing an exaggerated and aesthetically warped portion. So what makes the show Korean? Such questions are not new, especially for Korean films. A close look at Korean film history indicates that the country’s film industry was particularly preoccupied with the idea of a Korean national identity, especially under Japanese colonialism (1910-1945). In this dissertation, I examine films that portray masculinity as a national myth, including popular blockbusters or films set in modern Korea that have been excluded from or ignored in previous discussions of national cinema that focused on historical content. I argue that Korean national cinema depends upon the myth of masculinity; to be a Korean national film, a film must engage with this myth.
Keywords: Korean films; Korean media; masculinity; national film; postcolonial; Train to Busan